Morfofisiologia e composição químico-bromatológica dos cultivares brs massai e brs tamani sob épocas de vedação e idades de utilização - Fontinele, Renato Gomes (2018)
This study aimed to evaluate the influence of the deferment time and the age of use on gas exchange, morphogenesis, structural components, forage mass and chemical composition of the cultivars BRS Massai and BRS Tamani. The experiment was conducted at Embrapa Goats and Sheep in Sobral, State of Ceará, from March to October 2016. This was a 2x2x3 factorial randomized complete-block experimental design, with BRS Massai and BRS Tamani deferred at rainy and transition periods and used at the ages of 40, 80 and 120 days. The highest (1.10 μmol.m-2.s-1) rates of leaf photosynthesis were recorded in the BRS Massai cultivar at the age of use of 40 days. After this period the photosynthetic rates fell and remained the same. In both cultivars the highest (1.54 cm.perf-1.dia-1) leaf elongation rate occurred in the rainy season deferment and was used at the age of 40 days, and the highest production rates (111.10 kg.day-1) and forage accumulation (83.70 kg.day-1). The highest phyllochron (25.20 days. Leaf-1) occurred at 120 days of sealing at the transition time for the BRS Massai cultivar. The lowest (1.30) tipping index occurred in the cultivar BRS Massai deferred at the time of transition and used at the age of 40 days. The highest (5720 kg of MS.ha-1) total forage biomass was observed in the rainy season for both cultivars. Among the studied cultivars, the highest (1.42) leaf blade/stem ratio was observed in BRS Tamani. The use of grasses at the age of 40 days after the deferment in the rainy season did not affect the crude protein content (9.62% in DM) for the cultivars studied. In both cultivars, it is recommended the deferment in the rainy season and use in the ages of 40 to 80 days, above that period the losses by deterioration and disappearance of forage in the Brazilian semiarid are maximized.